2021
DOI: 10.1186/s12893-021-01320-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of primary arthrodesis versus open reduction and internal fixation in patients with Lisfranc fracture instability (The BFF Study) study protocol for a multicenter randomized controlled trial

Abstract: Background The Lisfranc injury is a complex injury of the midfoot. It can result in persistent pain and functional impairment if treated inappropriately. In Lisfranc fracture dislocation, treatment options are primary arthrodesis of the midfoot joints or open reduction and internal fixation. The purpose of the proposed study is to define the optimal treatment for the Lisfranc fracture dislocation, either primary arthrodesis or open reduction and internal fixation, in regard to quality of life, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…17 To further elucidate this area of concern, van den Boom et al is currently leading an ongoing multicenter randomized controlled trial (RCT) evaluating cost-effectiveness of PA versus ORIF for Lisfranc injuries. 18…”
Section: Discussionmentioning
confidence: 99%
“…17 To further elucidate this area of concern, van den Boom et al is currently leading an ongoing multicenter randomized controlled trial (RCT) evaluating cost-effectiveness of PA versus ORIF for Lisfranc injuries. 18…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 24 Both methods have advantages and disadvantages, though PA may be considered as the treatment of choice in pure ligamentous injuries. 23 Although previous studies have not demonstrated a significant difference, PA may demonstrate a trend towards less subsequent secondary surgery, less implant removal, and a faster return to activity, with some evidence of better functional outcomes, 5 , 7 - 9 , 11 , 13 , 16 , 18 , 21 , 24 preventing the need for secondary interventions and reducing the probability of developing posttraumatic arthritis. 5 , 9 , 13 , 20 ORIF risks development of secondary arthritis in 40% to 90% of patients and the possibility of costly secondary interventions such as removal of the osteosynthesis materials for pain relief or subsequent arthrodesis.…”
Section: Introductionmentioning
confidence: 95%
“… 10 , 15 However, preserving patency of the midfoot joints through ORIF with staged removal of hardware may improve functional mobility and thereby quality of life. 23 …”
Section: Introductionmentioning
confidence: 99%